2012
DOI: 10.3109/0886022x.2012.734429
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio in Evaluation of Inflammation in Patients with Chronic Kidney Disease

Abstract: Aim: The current data have proven the pivotal role of inflammation in the development of atherosclerosis and cardiovascular diseases in patients with chronic kidney disease (CKD). Neutrophil to lymphocyte (N/L) ratio has increasingly been reported as a measure of systemic inflammation. This study assessed N/L ratio and investigated its associations with standard inflammatory biomarkers in different stages of CKD patients. Material and methods: This cross-sectional study included 30 predialysis, 40 hemodialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
122
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 27 publications
12
122
4
3
Order By: Relevance
“…They release several types of cytokines and trigger the immune system and infl ammatory reactions. Previous studies have demonstrated that higher levels of NLR are associated with impaired cardiovascular outcomes (10)(11)(12)(13). NLR is not only associated with CVD, but also associated with chronic renal disease and several malignancies (11,13,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They release several types of cytokines and trigger the immune system and infl ammatory reactions. Previous studies have demonstrated that higher levels of NLR are associated with impaired cardiovascular outcomes (10)(11)(12)(13). NLR is not only associated with CVD, but also associated with chronic renal disease and several malignancies (11,13,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio (NLR) which can be derived from the white blood cell count is an inexpensive, routinely used, reproducible test. NLR has been proposed as a novel biomarker for systemic infl ammatory response in several diseases (10)(11)(12)(13). Previous studies have shown that NLR is associated with poor clinical outcomes in CVD and it is also a predictor for CVD (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that NLR is associated with other inflammatory markers such as TNF-alpha and CRP along with lower hemoglobin, albumin and total cholesterol. 5,6,22 Lower total cholesterol and albumin are likely to reflect a combination of nutritional status and chronic inflammation in hemodialysis patients. The associations between NLR and CRP as well as lower hemoglobin, albumin and cholesterol in the present study are in keeping with published literature.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent studies have demonstrated an association between the neutrophil-lymphocyte ratio (NLR) and pro-inflammatory cytokines including TNF-alpha and IL-6 levels in pre-dialysis and dialysis patients. 5,6 Unlike TNF-alpha and IL-6, which require separate tests, NLR can be readily calculated from a patient's full blood count without incurring additional cost. NLR has been identified as a marker of systemic inflammation and prognostic marker for mortality in patients with solid organ malignancies, 7 peripheral vascular disease, 8,9 and in the setting of acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…13 It causes not only cardiovascular disease, but also numerous chronic diseases such as cancers, diabetes mellitus, hypertension, connective tissue disease, and chronic kidney disease. [14][15][16][17][18] Figure 1: Receiver operating characteristic analysis for neutrophil-to-lymphocyte ratio to predict abnormal coronary angiography (area under curve is 0.726).…”
Section: Discussionmentioning
confidence: 99%